Local Knowledge for Environmental Protection and Climate Change Adaptation in Africa: Towards Decolonizing Climate Science - Nwaka, Geoffrey (Hamburger Journal für Kulturanthropologie (HJK), 2021)
The paper underscores the value and continuing relevance of indigenous and local knowledge for environmental protection and climate change adaptation in Africa. It argues that while Africa stands to gain from global science and international best practices, the continent should search within its own knowledge systems for appropriate ideas and approaches to many of its development challenges, and that indigenous knowledge may provide a model for rethinking and decolonizing climate science. Researchers and the development community should, therefore, try to tap into the vital resource of indigenous knowledge for locally appropriate and culture-sensitive ways to engage with the environment, and adapt to the negative impacts of climate change. The paper concludes with some general reflections on the indigenous knowledge movement as an appropriate local response to globalization and Western knowledge dominance, and as a way to underscore the fact of epistemic diversity and the need for inter-cultural dialogue.